2006
DOI: 10.1111/j.1467-8624.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Children's Attention to Environmental Messages About Groups: Social Categorization and the Origins of Intergroup Bias

Abstract: Abstract:The present study was designed to examine the effects of adults' labeling and use of social groups on preschool children's intergroup attitudes. Children (N = 87, aged 3 to 5) attending daycare were given measures of classification skill and self-esteem and assigned to membership in a novel ("red" or "blue") social group. In experimental classrooms, teachers used the color groups to label children and organize the classroom. In control classrooms, teachers ignored the color groups. After three weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
172
1
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 83 publications
10
172
1
13
Order By: Relevance
“…He, Baillargeon, and Premack (2011a) conducted a series of third-party experiments to address this question. Rather than using real-life social categories (e.g., categories based on age, race, gender, or language), He et al built on the well-established finding from social psychology that almost any salient basis for categorization, however minimal or arbitrary, can lead adults to categorize individuals into distinct social groups and foster preferential treatment of ingroup members (e.g., Ashbrun-Nardo, Voils, & Monteith, 2001;Brewer, 1999;Gregg, Seibt, & Banaji, 2006;Tajfel et al, 1971; for similar results with older children, see Dunham, Baron, & Carey, 2011;Master & Walton, 2013;Patterson & Bigler, 2006;Vaughan, Tajfel, & Williams, 1981). Accordingly, He et al created two novel social groups, using highly distinctive outfits as group markers, and asked whether 13-month-olds would detect a violation if a target individual helped an outgroup perpetrator who had stolen a toy from the target individual's ingroup member.…”
Section: Do Infants Expect Individuals To Co-retaliate Against Outgromentioning
confidence: 99%
“…He, Baillargeon, and Premack (2011a) conducted a series of third-party experiments to address this question. Rather than using real-life social categories (e.g., categories based on age, race, gender, or language), He et al built on the well-established finding from social psychology that almost any salient basis for categorization, however minimal or arbitrary, can lead adults to categorize individuals into distinct social groups and foster preferential treatment of ingroup members (e.g., Ashbrun-Nardo, Voils, & Monteith, 2001;Brewer, 1999;Gregg, Seibt, & Banaji, 2006;Tajfel et al, 1971; for similar results with older children, see Dunham, Baron, & Carey, 2011;Master & Walton, 2013;Patterson & Bigler, 2006;Vaughan, Tajfel, & Williams, 1981). Accordingly, He et al created two novel social groups, using highly distinctive outfits as group markers, and asked whether 13-month-olds would detect a violation if a target individual helped an outgroup perpetrator who had stolen a toy from the target individual's ingroup member.…”
Section: Do Infants Expect Individuals To Co-retaliate Against Outgromentioning
confidence: 99%
“…From 4-5 years, children favor those sharing transient features, arbitrarily assigned colored teams such as blue vs. red team that minimally define "in-group" characteristics (Patterson & Bigler, 2006). In the preschool years, such minimal group affiliation can determine significant social preference and in-group favoritism at both explicit and implicit levels (Dunham, Baron, & Carey, 2011).…”
mentioning
confidence: 99%
“…Indeed, both Ichheiser (1949) and Allport (1954Allport ( /1979 had once suggested that the visible differences can imply to the perception of real differences between racial and ethnic groups. The explicit labelling used by adults, such as teachers (Bigler, Brown, & Markell, 2001;Patterson & Bigler, 2006), was also found to influence children's attitudes toward other groups such as in the case of the Jewish children towards Arab (Bar-tal, 1996). Specifically, the explicit use of labelling by adults or authority figures allowed children to create links between the implicit messages, such as classroom posters, with the groups' social status (Bigler et al, 2001).…”
Section: The Developmental Intergroup Theorymentioning
confidence: 99%